Preoperative Planning Using 3D Printing as a Way to Improve the Outcomes of Surgical Treatment for Pilon Fractures - A. B. Koshkin; M. V. Parshikov; S. V. Novikov; A. A. Prokhorov; A. M. Fai (Неотложная медицинская помощь, 2024)
RELEVANCE. Despite the development of modern diagnostic methods, osteosynthesis instruments and rehabilitation, surgical management of distal tibia fractures remains a great problem due to the high complication rate leading to permanent disability, such as problems with soft tissue healing, infectious complications, post-traumatic arthrosis of the ankle joint. These complications are associated with the high incidence of high-energy injuries, soft-tissue envelope features, and the wide range of movements in the ankle joint. At the same time, in the treatment for comminuted intra-articular pilon fractures, there is no clearly defined operation algorithm: choice of access, reduction and fixation techniques. Recently, when planning osteosynthesis, additive technologies have become increasingly widespread, in particular, 3D printing of full-size fracture prototypes.   AIM OF STUDY. To analyze preoperative planning methods of osteosynthesis in pilon fractures and evaluate 3D-printing for the improvement of surgical treatment of pilon fractures.   MATERIAL AND METHODS. The literature search was carried out in the databases of medical publications: PubMed, eLibrary, Cyberleninka. The search was performed using the following terms: pilon fractures, osteosynthesis, preoperative planning, 3D-printing, 3D-model, and the corresponding terms in Russian.   RESULTS. According to various authors, the use of 3D printing in preoperative planning improves the parameters of operative duration, reduction quality, functional outcome, intraoperative blood loss, and reduces the number of complications.   CONCLUSIONS. Evaluation of the long-term results of using 3D printing in preoperative planning for osteosynthesis in pilon fractures is ongoing. But even now we can draw conclusions about the prospects of the method and recommend it for widespread use in the routine practice of the orthopedic traumatologist.